First and Subsequent Lifetime Alcoholism and Mental Disorders in Suicide Victims With Reference to a Community Sample—the Lundby Study 1947–1997 - Holmstrand, Cecilia; Bogren, Mats; Mattisson, Cecilia; Brådvik, Louise (Frontiers in Psychiatry, 2018)
Background: Suicide victims have been found to frequently suffer from mental disorders, often more than one, and comorbidity has also been found to be a risk factor for suicide. The aim of the present study was to determine the first disorder and possible subsequent disorders in suicide victims during their lifetimes and to compare their development with the development of mental and alcohol use disorders in a community sample. Methods: The Lundby Study is a prospective longitudinal study of mental health in a general population comprising 3563 subjects, including 68 suicide victims, followed by four field investigations from 1947 to 1997; mortality was monitored up to 2011. Results: Alcohol use disorder (AUD) was most common as a first diagnosis (26/68, 38.2%) among suicide victims, followed by ‘depression’ (20/68, 29.4%) and ‘anxiety’ (7/68, 10.3%). A predominance of AUD as a first diagnosis was found in the male group, whereas ‘depression’ was the most common first diagnosis in the female group. However, there were very few females with AUD in the Lundby Study. In the whole population, it was more common for someone who started with an AUD to develop a subsequent mental disorder than the other way around. The same was true for AUD in relation to depression. Conclusions: AUD was the most common first mental disorder among male suicide victims and could thus be considered a starting point in the suicidal process. We propose that in addition to detecting and treating depression, it is important to detect and treat AUD vigorously and to be alert for subsequent depressive symptoms and other mental disorders in suicide prevention efforts.